Genetic deletion of TRPA1 receptor attenuates amyloid beta- 1-42 (Aβ1-42)-induced neurotoxicity in the mouse basal forebrain in vivo. (July 2020) - Payrits, M.; Borbely, E.; Godo, S.; Ernszt, D.; Kemeny, A.; Kardos, J.; Szoke, E.; Pinter, E.
Highlights: Aβ1–42 injection evokes severe neurotoxicity with memory loss in TRPA1 +/+ mice. Cholinergic fibre and cell body loss were significantly attenuated in TRPA1 −/− mice. TRPA1 −/− animals show substantially reduced memory loss after Aβ1–42 -injection. TRPA1 may play deteriorating role in the Aβ1–42 -induced cholinergic neurotoxicity. Abstract: Amyloid β 1–42 peptide (Aβ1–42 ) accumulates in Alzheimer's disease (AD) that is toxic to the basal forebrain cholinergic (BFC) neurons in substantia innominata-nucleus basalis magnocellularis complex (SI-NBM). Transient Receptor Potential Ankyrin1 (TRPA1) receptor is present in murine brain, however its role in neurotoxic processes is unclear. We investigated the Aβ1–42 -induced neurotoxicity in TRPA1 wild-type (TRPA1 +/+ ) and knockout (TRPA1 −/− ) mice. Expression and neuroanatomical localization of TRPA1 receptor were examined using RT qPCR. Cholinergic fibre loss was determined on acetylcholinesterase (AChE) stained brain slices, and choline acetyltransferase (ChAT) immunohistochemistry was used to assess the cholinergic cell loss. Novel object recognition (NOR), radial arm maze (RAM) and Y-maze tests were used to investigate memory loss. Aβ1–42 -injected WT mice showed marked loss of cholinergic fibres and cell bodies, which was significantly attenuated in TRPA1 −/− animals. According to the NOR and RAM tests, pronounced memory loss was detected in Aβ1–42 -injected TRPA1 +/+ mice, but not in TRPA1 −/− group. Our findings demonstrate that TRPA1 KO animals show substantially reduced morphological damage and memory loss after Aβ1–42 injection in the SI-NBM. We conclude that TRPA1 receptors may play an important deteriorating role in the Aβ1–42 -induced cholinergic neurotoxicity and the consequent memory loss in the murine brain.